2018
DOI: 10.3892/etm.2018.5811
|View full text |Cite
|
Sign up to set email alerts
|

Expression and secretion of neuregulin-1 in cardiac microvascular endothelial cells treated with angiogenic factors

Abstract: Abstract. Neuregulin-1 (NRG-1) is a positive regulator of angiogenesis, which suggests there may be an association between NRG-1 and angiogenic factors. The aim of the present study was to investigate the effect of treating human cardiac microvascular endothelial cells (HCMECs) with angiogenic factors on NRG-1 expression and secretion. HCMECs were cultured and stimulated with vascular endothelial growth factor (VEGF; 100 ng/ml), angiopoietin (Ang)-1 (100 ng/ml) or Ang-2 (100 ng/ml) under normal or hypoxia/seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…In the myocardium, NRG1 is primarily produced by the microvascular endothelium in response to mechanical stretch, oxidative stress, and hypoxia . NRG1/ErbB signalling and NRG1 are suggested to increase the number of microvessels in post‐ischaemic animal models . Further, demonstrating the link between endothelial dysfunction and oxidative stress, we found that NRG1‐β correlated with the oxidative stress marker IGFBP‐1 in our patients with HFrEF.…”
Section: Discussionsupporting
confidence: 57%
“…In the myocardium, NRG1 is primarily produced by the microvascular endothelium in response to mechanical stretch, oxidative stress, and hypoxia . NRG1/ErbB signalling and NRG1 are suggested to increase the number of microvessels in post‐ischaemic animal models . Further, demonstrating the link between endothelial dysfunction and oxidative stress, we found that NRG1‐β correlated with the oxidative stress marker IGFBP‐1 in our patients with HFrEF.…”
Section: Discussionsupporting
confidence: 57%
“…HER2 is essential throughout the cardiovascular system [11][12][13], and its extracellular domain shedding process make it highly expressed in the bloodstream [5]. Of note, our data showed that the difference in circulating HER2 levels between CAD and control groups was not strikingly huge.…”
Section: Discussionmentioning
confidence: 63%
“…HER2 is abundantly expressed throughout the cardiovascular system, including by endothelial cells, vascular smooth muscle cells (SMCs), and cardiomyocytes [11][12][13]. Previous studies found that the HER family, particularly EGFR and HER2, contribute to the pathogenesis of vascular remodeling and atherosclerosis, such as oxidative stress, macrophage infiltration, and SMC proliferation and migration [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…11) However, another study has revealed that the expression and release of NRG-1 were significantly increased in human cardiac microvascular endothelial cells under VEGF and Ang-1 stimulation, which suggested that these angiogenic factors could regulate NRG-1 signaling pathway. 14) Although there is no conclusion of the precious casual association among VEGF, Ang-1, and NRG-1, we can speculate that there may be a positive feedback among VEGF/ Ang-1-NRG-1 signaling pathways. Consistent with these findings, our results have demonstrated that NRG-1, VEGF, and Ang-1 were all significantly increased in good CCC group, and there was a positive correlation among them.…”
Section: Discussionmentioning
confidence: 80%
“…13) In addition, NRG-1 has been shown to promote myocardial angiogenesis in the ischemic and diabetic myocardium and is involved in the vascular endothelial growth factor (VEGF) / Angiopoietin-1(Ang-1) angiogenesis signaling events. 11,14,15) These findings revealed that NRG-1 might participate in the development of CCC and could function as a potential biomarker. However, the association between NRG-1 and CCC has not been explored in CAD patients.…”
mentioning
confidence: 74%